2007
DOI: 10.1007/s10800-007-9451-9
|View full text |Cite
|
Sign up to set email alerts
|

Electroless deposition of ternary Ni–P alloy coatings containing tungsten or nano-scattered alumina composite on steel

Abstract: The performance of ternary electroless deposited Ni-P-W and Ni-P-alumina composite coatings on low carbon steel substrates was studied. The effect of experimental parameters, such as temperature, pH, nickel sulfate concentration, sodium hypophosphite concentration, sodium citrate concentration, and deposition time on the deposition rate were investigated. The coating brightness, coherence, and uniform surface distribution were improved due to addition of W and alumina. The coating performance was evaluated bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 22 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…At 600 C, the hardness and wear resistance of Ni-W-P coatings is decreased. Hamdy et al 33 have observed that the weight loss due to wear is decreased with increase in incorporation rate of alumina particles in the coating. From Fig.…”
Section: Behavior Of Ni-p-tio 2 Composite Coatingsmentioning
confidence: 99%
“…At 600 C, the hardness and wear resistance of Ni-W-P coatings is decreased. Hamdy et al 33 have observed that the weight loss due to wear is decreased with increase in incorporation rate of alumina particles in the coating. From Fig.…”
Section: Behavior Of Ni-p-tio 2 Composite Coatingsmentioning
confidence: 99%
“…1,2 Co-deposition of solid lubricants such as polytetrafluoroethylene (PTFE), [3][4][5] MoS 2 , 6-8 graphite, 9 and carbon nanotubes 10,11 into the EN coating improves its tribological properties by reducing friction coefficient. Although PTFE provides a very low friction coefficient, EN-PTFE composite coatings are not expected to be useful in heavy-duty applications because PTFE is a soft polymer and does not have a layered structure like graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten, being a metal with a high melting point, improves the high temperature resistance of coatings based on nickel. The three-component tungsten-containing nickel coatings described in the literature are characterized by good mechanical properties and elevated corrosion resistance [10,12,18,19,41]. Zirconium(IV) oxide is a very hard (9 on Mohs scale of hardness) powder resistant to aggressive chemical compounds.…”
Section: Introductionmentioning
confidence: 99%